Konsumsi Meal Replacement Dan Kadar Glukosa Darah Pasien Dm Tipe II - Kiki Riskianti; Suhaema Suhaema; Fifi Luthfiyah (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background: The world's population is suffering from diabetes increased from year to year. DM is the most outpatients in Mataram City Hospital for a total of 517 patients. The principle of meal planning for diabetics is a balanced diet.  The results of initial survey showed 8 of 10 people consumed a meal replacements. Objective: to determine the relationship of the consumption of meal replacements  with blood glucose levels of type 2 DM outpatient in general hospital of Mataram City.Methods: This study was an observational analytic with crossectional design. To determine the relationship of the independent variables and the dependent variable statistical analysis used Spearman Rank correlation test with a significance level of 5%. Results: The total sample is 69 people, aged> 45 years (89.9%), women (65.2%). Most physical activity (50.7%) <150 minutes / week, overweight (59.4%), diabetes mellitus onset 1-3 years ago (66.7%). Comsumption levels : less energy consumption rate (44.9% ), the normal level of carbohydrate (58.0%), less fiber (100%). Meal replacement that is consumed is Diabetasol (85.7%), the amount of consumption of meal replacements <1 portion/serving (78.6%), with  ≥1 times / day (39.1%). Control of glucose levels most (71%) in the poor category, the average blood glucose sample is 170.3 mg/dL. Relationship of a consumption of meal replacement with blood glucose levels was not significant (p= 0,191) Conclusion:  Relationship of a consumption of meal replacement with blood glucose levels were not significantly.